The Botswana Bushmen’s Fight for Water & Land Rights in the Central Kalahari Game Reserve - Winters, Olivia Jane (Consilience, 2015)
The Botswana Bushmen live in the Central Kalahari Game Reserve in the center of Botswana. The area is known to be one of the most rugged, arid landscapes on the face of the planet. In recent years, due to claims from the Botswana government that the Bushmen needed to ‘develop’, extreme efforts have been made to force the Bushmen from the reserve originally allotted to them in the 1960s.